Boron induces seed germination and seedling growth of Hordeum vulgare L. under Nacl stress (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
Boron (B), an essential micronutrient, helps the plants to complete their life cycle successfully. Therefore, the present experiment was conducted to study (1) the role of B in seed germination and seedling growth, (2) the toxicity effect of B in seed germination and seedling growth and (3) the role of B in tolerance of barley (Hordeum vulgare L. var. ‘Bakore’) to NaCl stress. Under NaCl stress and non-stress conditions, application of high levels of B (100 µM) decreased parameters of germination (G%, VI, GI and MGT), growth (RL, SL, RFW, SFW, RDW and SDW), except the accumulation of Pro and MDA in barley seedlings. Also, a fluorescence study reveals that production of ROS (H2O2 and O2 •—) and non-viable cells increased in roots of barley seedlings treated with NaCl and high dose of B. An alteration in anatomical structure of barley seedlings was observed with the application of NaCl and high dose of B. However, a low concentration of B (50 µM) proved best and increased all germination and growth traits of barley seedlings by increasing further accumulation of Pro. Also, 50 µM of B significantly increased the biosynthesis of photosynthetic pigments (Chl a, b and total Chl) and deceased formation of ROS and viable cells in roots. Therefore, concluded that sufficient dose of B could be beneficial for barley plant in improving the tolerance to NaCl stress.